STUDI INTERNALISASI NILAI-NILAI ISLAM MODERAT DI PESANTREN MAMBAUS SHOLIHIN 4 MASOHI, MALUKU TENGAH - Hafshoh, Siti chufsoh; Ali Ahmad Yenuri (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2025)
The notion of radicalism and liberalism that widespread in the globalization era make the Islamic boarding schools need to improve the moderate values. The objectives of this research are to explain the teaching, imitation, and the impact of instilling the moderate values through pesantrenbased education at PP Mambaus sholihin 4 masohi, maluku tengah. The research was field research with qualitative methods. The data collection method was done by interview, observation, and documentation. The results of this research showed that: (1) The internalization through teaching aswaja values, namely tasamuh, tawasuth, tawazun, and amar ma'ruf nahi munkar, in Islamic boarding schools used the method of recitation, lectures, discussion or bahtsul masail as well as using teaching resources and media in the form of turats. (2) The imitation of aswaja values as a method in the internalization stage is done by Kyai, and teachers in daily activities have been taught and exemplified to the students in the form of refraction in the boarding school. (3) The formation of a moderate attitude of santri is the impact of internalizing the values of tasamuh, tawasuth, tawazun and amar ma'ruf nahi munkar, which are internalized in Islamic boarding schools to know who they are by not taking sides with extreme radical or otherwise liberal understandings.